Three Weekly Intra-Articular Injections of Hylan G-F 20 vs Arthrocentesis in Patients with Chronic Idiopathic Knee Osteoarthritis: A Multicenter, Evaluator- and Patient-Blinded, Randomized Controlled Trial - Yili Huang, DO; Peter Lascarides, DO; Wilson Ngai, PharmD, MSc, MBA; Kevin Steele, PharmD, MHA; Charles D. Hummer, MD (Elsevier, 2023)
ABSTRACT: Background: Knee osteoarthritis is a leading cause of disability worldwide. Symptoms can vary over time, leading to episodes of worsened symptoms known as flares. Intra-articular injection of hyaluronic acid has demonstrated long-term symptomatic relief in the broader knee osteoarthritis population, although its use in the flare population has not been extensively examined. Objective: To assess the efficacy and safety of 3 once-weekly intra-articular injections of hylan G-F 20 (as single and repeat courses) in patients with chronic knee osteoarthritis, including a subpopulation that experienced flare. Methods: Prospective randomized controlled, evaluator- and patient-blinded, multicenter trial with 2 phases: hylan G-F 20 vs arthrocentesis only (control) and 2 courses vs single-course hylan G-F 20. Primary outcomes were visual analog scale (0-100 mm) pain scores. Secondary outcomes included safety and synovial fluid analysis. Results: Ninety-four patients (104 knees) were enrolled in Phase I, with 31 knees representing flare patients. Seventy-six patients (82 knees) were enrolled in Phase II. Long-term follow-up was 26 to 34 weeks. In flare patients, hylan G-F 20 showed significantly more improvement than the controls for all primary outcomes except pain at night (P = 0.063). Both 1 and 2 courses of hylan G-F 20 showed significant improvements from baseline for primary outcomes with no differences in efficacy between groups in the intention-to-treat population at the end of Phase II. Two courses of hylan G-F 20 showed better improvement in pain with motion (P = 0.0471) at long-term follow-up. No general side effects were reported, and local reactions (pain/swelling of the injected joint) resolved within 1 to 2 weeks. Hylan G-F 20 was also associated with reduced effusion volume and protein concentration. Conclusions: Hylan G-F 20 significantly improves pain scores vs arthrocentesis in flare patients with no safety concerns. A repeat course of hylan G-F 20 was found to be well tolerated and efficacious.